Analysis of Weed Diversity in Maize (Zea mays L.) Field at Lowland and Highland Areas - Maulana, Arman Adrian; Fatmasari, Yulia; Aprilia, Larasita; Purnamasari, Niken Ayu; Hanafi, Imam; Tarigan, Puji Lestari (Universitas Sam Ratulangi, 2025)
Weeds are very detrimental to maize because they compete for light, water and nutrients. This observation aims to determine the composition and structure of weeds on narrow leaves on corn cultivation land in the lowlands, namely in the Saworatap area, Gedangan subdistrict and the highlands in Randuagung village, Wonosari subdistrict, Malang. This observation was carried out in November 2024. The method used in this observation was survey and sample collection techniques were purposive sampling, making plots measuring 1 m x 1 m with a total of 6 plots in both locations. In the lowlands, the composition of grass weeds is only two species, namely Eleusine indica and Setaria verticillata which belong to the Poaceae family. The composition of grass weeds in the highlands has a higher species diversity, namely six species divided into two families. Weed species belonging to the Poaceae family are Echinochloa colona, ​​Setaria verticillata, Eleusine indica, and Chrysopogon zizanioide, while grass weeds belonging to the Cyperaceae or enigma family are Cyperus iria and Cyperus rotundus.